Modelling the behaviour of reinforced concrete beams strengthened with FRP - Neto, Pedro (2006)
The strengthening of reinforced concrete structures with fiber reinforced polymers (FRP) is particularly attractive due to their mechanical properties. The understanding of the premature failure modes is of great importance. Since rupture is frequently found to occur at the interface FRP concrete, there is a clear need to study the nature of the bonding so as to develop techniques to permit its design modeling. The stress distribution in shear test models does not precisely match the one obtained in flexural reinforcement; in the latter, according to various authors [1, 2], in addition to the stresses tangential to the interface, normal stresses are also important. In this paper, a numerical model is presented to describe the behavior of reinforced concrete beams strengthened with FRP. This model is based on previous studies focused both on: i) the distribution of shear stresses at the interface FRP concrete and on ii) the stress concentration at the plate ends in flexural models. Furthermore, the importance of the flexural cracks in the premature rupture of the element is also analyzed. The behavior of reinforced c concrete beams strengthened with both FRP laminates and sheets is considered. The FRP epoxy concrete arrangement and the flexural cracks are modeled with interface elements with initial zero thickness, using a discrete approach and a localized damage model. A softening behavior is adopted to simulate the stress transfer along the FRP- -concrete interface. The importance of considering the mixed mode of fracture is discussed. Mention is also made to some of the main mathematical models found in the literature.